Effects of Teacher Autonomy Support Intervention on Thai Students' Motivation: A Self Determination Theory Perspective - Amrita, Kaur (2011)
Self Determination Theory (SDT) postulates that Teacher’s Autonomy Support (TAS) promotes learning motivation and academic outcomes, but cross cultural controversies within SDT question the significance of TAS in Asian classrooms. The present research tests the relevance of TAS on Thai students’ motivation in relation to Thai Education reforms. In a quasi-experimental non-equivalent group design, 103 students (56 girls and 47 boys) of Grade-6, from a Thai public school, participated in the present study. The experimental group underwent an autonomy supportive intervention for seven (7) sessions (60 minutes each) in a regular classroom setting by a trained teacher. Data were gathered for the Pretest, posttest1 and posttest2 using an intrinsic motivation inventory by Ryan (1982), a self-regulation questionnaire by Ryan and Connell (1989) and a learning climate questionnaire by Black and Deci (2000) for variables which include interest, effort, pressure, relatedness, perceived autonomy support, identified and external regulation. An analysis using Multivariate Analysis of Variance in the pretest showed no significant difference between the experimental group and the control group on all variables including gender. However, significant mean differences were observed in the following cases: (i) between both groups at the postest1, (ii) between the pretest and postest1 of the experimental group, with the main effects observed for all variables as a result of TAS and (iii) between means of the postest1 and postest2 in the experimental group. However, the main effects were only significant for variables such as effort, relatedness and perceived autonomy support. Thus, the findings have strengthened the SDT belief that autonomy is not a culturally bound value and is equally relevant for Thai students and has implications for Thai education and its policies.